Unveiling the Angiotensin-(1–7) Actions on the Urinary Bladder in Female Rats - Lamy, Gustavo B.; Cafarchio, Eduardo M.; do Vale, Bárbara; Antonio, Bruno B.; Venancio, Daniel P.; de Souza, Janaina S.; Maciel, Rui M.; Giannocco, Gisele; Silva Neto, Artur F.; Oyama, Lila M.; Aronsson, Patrik; Sato, Monica A. (Frontiers in Physiology, 2022)
Angiotensin-(1-7) is a peptide produced by cleavage of Angiotensin I by angiotensin converting enzyme 2 (ACE-2), and binds to Mas receptors localized in different cells throughout the body. It is still unknown if angiotensin-(1-7) exerts any action in the urinary bladder (UB). We investigated the effects of intravenous and topically (in situ) administration of Angiotensin(1-7) on intravesical pressure (IP) and cardiovascular parameters. In addition, the gene and protein expression of Mas receptors and ACE-2 was evaluated in the UB. Adult female Wistar rats anesthetized with 2% isoflurane in 100% O2 were submitted to the cannulation of the femoral artery and vein for mean arterial pressure (MAP) and heart rate (HR) recordings, and infusion of drugs, respectively. The renal blood flow was measured using a Doppler flow probe placed around the left renal artery. The UB was cannulated for IP recording. We observed that angiotensin-(1-7) either administrated by intravenous injection (115.8±28.6% vs. -2.9±1.3% saline) or topically (147.4±18.9% vs. 3.2±2.8%) onto the UB evoked a significant (p<0.05) increase in IP compared to saline and elicited no changes in MAP, HR and renal conductance. The marked response of angiotensin-(1-7) on the UB was underpinned by qPCR and Western Blotting assay, which demonstrated the mRNA and protein expression of Mas receptors in the bladder, respectively. ACE-2 mRNA and protein expression was also observed in the bladder. Therefore, the findings demonstrate that angiotensin-(1-7) acts in the UB to increase the IP and suggest that this peptide can be also locally synthetized in the UB.